Strengthening SSL Security with attribute certificate - Kumar, Rajesh; Rekha, K (EAI Endorsed Transactions on Cloud Systems, 2018)
Now-a-days many people do multiple activities, transactions in fields such as finance, banking, business sector etc over internet. These activities, transaction should be secure. Providing security and authorization control has became the major concern in the globalization of internet. We are inspired by the need and urgency to handle the present situations and to put forward a strong authorization methodology in the globalization of web environment. Public Key Infrastructure which we are using now is meant to provide strong authentication by the use of digital certificates. In this paper we introduce a new technology of Privileged Management Infrastructure which provides strong authorization by the use of attribute certificates. Also in order to introduce attribute certificate we primarily need to check the genuineness of SSL digital certificate i.e. whether the SSL digital certificate is genuine or it’s a fake certificate.
Keywords: SSL; Attribute Certificate; PMI; PKI